Engeletin ameliorates pulmonary fibrosis through endoplasmic reticulum stress depending on lnc949-mediated TGF-β1-Smad2/3 and JNK signalling pathways. (1st January 2020) - Zhang, Jinjin; Chen, Xiaoqing; Chen, Hongbin; Li, Rongrong; Xu, Pan; Lv, Changjun; Liu, Bo; Song, Xiaodong
Abstract: Context: Pulmonary fibrosis (PF) is a highly heterogeneous and lethal pathological process having no effective drug. Engeletin exerts multiple biological activities including anti-inflammatory and lung repair. Whether engeletin has therapeutic effects on PF remains unclear. Objective: Examining effect and mechanism of engeletin on PF in vivo and in vitro. Materials and methods: L929 cells (1 × 10 6 /well) were treated with TGF-β1 (5 ng/mL). Sixty male C57BL/6 mice were divided into three groups and given saline or single intratracheal instillation bleomycin (5 mg/kg) or both bleomycin and intraperitoneally injected engeletin (25 mg/kg). Results: Histological staining showed engeletin inhibited myofibrobasts activation and improved alveolar structure. Engeletin elevated forced vital capacity from 12 induced by bleomycin to 17. CCK-8 assay reported IC50 value of engeletin was 270 μg/mL. Real-time cellular analysis showed engeletin reduced proliferation and migration of myofibroblasts by 2.5- and 2-fold. Engeletin blocked α-SMA, vimentin, and collagen expression. RNA sequencing revealed PERK-ATF4 signalling pathway relating to ER stress involved in anti-fibrotic function of engeletin. Engeletin reduced ATF4, CHOP and BIP expression. Chemical inhibitors of smad2/3- (SB431542) and JNK- (SP600125) signalling pathways blocked expression of long noncoding RNA (lncRNA) – lnc949. Engeletin inhibited phosphorylation of smad2/3 and JNK leading to lower level of lnc949. Knockdown lnc949 inhibited ATF4, CHOP and BIP expression. Conclusions: We reported gene expression profiling of engeletin through RNA-seq; and identified lnc949-mediated TGF-β1-Smad2/3 and JNK were upstream signalling pathways of ER stress induced by engeletin. Our results showed engeletin remedies pulmonary fibrogenesis and may be a new drug candidate.